2019
DOI: 10.4300/jgme-d-18-00308.1
|View full text |Cite
|
Sign up to set email alerts
|

ACGME Milestones Within Subspecialty Training Programs: One Institution's Experience

Abstract: Background The Accreditation Council for Graduate Medical Education Milestones were created as a criterion-based framework to promote competency-based education during graduate medical education. Despite widespread implementation across subspecialty programs, extensive validity evidence supporting the use of milestones within fellowship training is lacking.Objective We assessed the construct and response process validity of milestones in subspecialty fellowship programs in an academic medical center.Methods Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The 11 subcompetencies included a combination of ''context-independent'' and ''context-dependent'' subcompetencies. 23 Context-independent subcompetencies are those in which the assessment of Milestone levels should not change based on the context of the training environment. As noted by Heath et al, the competencies of professionalism and interpersonal and communication skills are examples of context-independent subcompetencies.…”
Section: Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 11 subcompetencies included a combination of ''context-independent'' and ''context-dependent'' subcompetencies. 23 Context-independent subcompetencies are those in which the assessment of Milestone levels should not change based on the context of the training environment. As noted by Heath et al, the competencies of professionalism and interpersonal and communication skills are examples of context-independent subcompetencies.…”
Section: Interventionsmentioning
confidence: 99%
“…As noted by Heath et al, the competencies of professionalism and interpersonal and communication skills are examples of context-independent subcompetencies. 23 In contrast, the subcompetencies of patient care and medical knowledge are examples of contextdependent subcompetencies for which the assessment of Milestone levels may change based on the context of the training environment. 23 Other subcompetencies in systems-based practice and practice-based learning and improvement are more ambiguous.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interprogram variability has been reported, as has variability between specialties. 9,10 In terms of milestone accuracy within a particular evaluation, Beeson et al evaluated the rate of "straight line scoring" (SLS, defined as a resident being assigned the same score across milestone subcompetencies) and showed that a small but meaningful number of programs submitted SLS ratings. Because of the statistical improbability of SLS, any SLS ratings reduce the validity assertions of the milestone assessments.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure they met the needs of physicians, trainees, and society at large, the ACGME committed to ongoing data collection and review, with the opportunity for future revisions. Feedback from educators, program directors, and trainees, with additional input from qualitative and quantitative research, highlighted the benefits and challenges of the original Milestones within the subspecialties ( 3 , 5 , 10 , 11 ). In PCCM and other fields, this system appeared to achieve construct validity based on the year-by-year upward trajectory of milestone ratings among fellows ( Figure 3 ) ( 12 ).…”
mentioning
confidence: 99%